A modified inertial proximal gradient method for minimization problems and applications - Kesornprom, Suparat; Cholamjiak, Prasit (AIMS mathematics, 2022)
In this paper, the aim is to design a new proximal gradient algorithm by using the inertial technique with adaptive stepsize for solving convex minimization problems and prove convergence of the iterates under some suitable assumptions. Some numerical implementations of image deblurring are performed to show the efficiency of the proposed methods.